Mediating the dream = Les genres et médias du rêve - Dieterle, Bernard; Engel, Manfred (Cultural dream studies, 2020)
Representations of dreams – no matter if factual or fictional – are influenced not only by cultural patterns but also by the specific opportunities offered and the specific challenges posed by the genre or medium which was chosen for them. The essays in the two volumes of this publication consider, in detailed case studies, variants of factual dream reports and fictional dreams in epic poems, dream visions, satires, the Chinese genre zhiguai, novels, lyrical poems, prose poems, dramas, dream plays, Japanese mugen no plays, radio plays, paintings, comics, films, video games, operas, and instrumental music. The authors and artists discussed include Artemidorus, Bachmann, Baudelaire, Bergman, Berlioz, Bertrand, Boulanger, Borchert, Burroughs, Calderón, Chaucer, de Chirico, Christine de Pizan, Eich, Gan Bao, Garnier, Handke, A. Hardy, Heine, Hitchcock, Homer, Jean Paul, Liu Xiang, Kurosawa, Levi, Liszt, Magritte, Matisse, Murnau, Nabokov, Redon, J. Renoir, Reverdy, Rimbaud, Quevedo, Saariaho, Sebald, Spiegelman, Swedenborg, Strindberg, Trakl, Valmiki, Vermeer, Virgil, R. Wagner, von Wysocki, Zeami, and many others.
Keywords: Aufsatzsammlung; Konferenzschrift -- 2018 -- Saarbrücken; Künste; Traum; Musik; Film; Literatur